2015
DOI: 10.1227/neu.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Minimally Invasive Sacroiliac Joint Fusion Using Triangular Titanium Implants vs Nonsurgical Management for Sacroiliac Joint Dysfunction

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 65 publications
2
122
0
3
Order By: Relevance
“…In contrast, EQ-5D score improvements in the CM group were minimal. The improvements in quality of life seen in our study mirror those seen in a prior randomized trial [43]. Our study, combined with the prior randomized trial and 4-and 5-year outcomes from both European [39] and US [45] cohorts, suggest that minimally invasive SIJ fusion can be added to the portfolio of spine surgeries proven safe and effective that European surgeons can offer their patients.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In contrast, EQ-5D score improvements in the CM group were minimal. The improvements in quality of life seen in our study mirror those seen in a prior randomized trial [43]. Our study, combined with the prior randomized trial and 4-and 5-year outcomes from both European [39] and US [45] cohorts, suggest that minimally invasive SIJ fusion can be added to the portfolio of spine surgeries proven safe and effective that European surgeons can offer their patients.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings both replicate and extend previous studies. In previously published case series [36][37][38][39], systematic reviews [40,41], a prospective multicenter clinical trial [42], and a recently published randomized clinical trial of similar design conducted in the USA [43], similar improvements in SIJ pain, self-rated limitations in activities due to pain (Oswestry Disability Index) and quality of life were observed in participants undergoing SIJF. Our study provides an additional, independent confirmation that the improvements after surgery are clinically important and statistically superior to those seen with continued conservative care.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[8][9][10]41,42 Specifically, the TPS implants were found to exhibit a substantial degree of bone ongrowth and ingrowth to their surfaces, resulting in a mechanically stable interface with surrounding host bone. The AM implants investigated herein provide a highly interconnected porous surface with an open fenestrated core structure that offers comparatively greater surface area for bony integration and the ability to be pre-packed with graft material, which may benefit a number of spinal implants, such as fusion, disc, and SI joint implants.…”
Section: Discussionmentioning
confidence: 99%
“…17 Responses in the non-surgical arms of two prospective randomized trials showed little, if any, improvement at 6 months. 18,19 Given the absence of published outcomes data supporting long-term pain relief from non-surgical treatment, patients with a diagnosis of SIJ pain who experience pain for a minimum of six months and who do not respond to an adequate course of non-surgical treatment may be considered for SIJ fusion.…”
Section: Introductionmentioning
confidence: 99%